2014
DOI: 10.1177/0003489414523561
|View full text |Cite
|
Sign up to set email alerts
|

OK432 Versus Doxycycline for Treatment of Macrocystic Lymphatic Malformations

Abstract: Objectives: A variety of sclerotherapy agents are used to treat macrocystic lymphatic malformations (LMs). This retrospective study at a single institution was performed to compare the outcomes of pediatric macrocystic LMs of the head and neck that were treated with doxycycline or with OK432. Methods:The outcomes measured included early response to therapy, number of treatments required, operating room time, and adverse events. Results:The rates of clinical success for OK432 and doxycycline were similar (83% a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 39 publications
(64 reference statements)
1
15
0
Order By: Relevance
“…The average pre-treatment volume varied between the different sclerosants but was not statistically significant (p=0.6618). Volumetric improvement was similar between the three sclerosing agents, with an average reduction of 84.5%, consistent with published literature 8 9. Ethanolamine had an average reduction in volume of 85.7% and OK-432 and doxycycline had an average reduction of 84.6% and 83.7%, respectively.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The average pre-treatment volume varied between the different sclerosants but was not statistically significant (p=0.6618). Volumetric improvement was similar between the three sclerosing agents, with an average reduction of 84.5%, consistent with published literature 8 9. Ethanolamine had an average reduction in volume of 85.7% and OK-432 and doxycycline had an average reduction of 84.6% and 83.7%, respectively.…”
Section: Resultssupporting
confidence: 88%
“…The outcome is consistent with that in the literature from many different sclerosants including OK-432, doxycycline, ethanolamine oleate, bleomycin, dextrose, ethanol, sodium tetradecyl sulfate, and acetic acid. The efficacy rates with these agents range from 62% to 100% 8 9. Published reports have shown that sclerotherapy is nearly four times more successful than surgical excision for treating LMs, at the same time carrying lower associated morbidity 10 17 30.…”
Section: Discussionmentioning
confidence: 99%
“…2,7,8 OK-432 is very effective and used widely, but it is unavailable in authors setting. 9 Doxycycline and bleomycin are readily available and cheap alternative. In this context, author planned this study to test the outcome and efficacy of using injection bleomycin and injection doxycycline in treating lymphatic malformation in a different group of patients.…”
mentioning
confidence: 99%
“…30,38 Since institutional review board approval is needed to use OK-432, and its efficacy is not superior to other sclerosants; its use in the United States is limited. 56…”
Section: Ok-432mentioning
confidence: 99%